Hydrocarbon Degradation in Caspian Sea Sediment Cores Subjected to Simulated Petroleum Seepage in a Newly Designed Sediment-Oil-Flow-Through System - Mishra, Sonakshi; Wefers, Peggy; Schmidt, Mark; Knittel, Katrin; Krüger, Martin; Stagars, Marion H.; Treude, Tina (Frontiers in Microbiology, 2017)
The microbial community response to petroleum seepage was investigated in a whole round sediment core (16 cm length) collected nearby natural hydrocarbon seepage structures in the Caspian Sea, using a newly developed Sediment-Oil-Flow-Through (SOFT) system. Distinct redox zones established and migrated vertically in the core during the 190 days-long simulated petroleum seepage. Methanogenic petroleum degradation was indicated by an increase in methane concentration from 8 µM in an untreated core compared to 2300 µM in the lower sulfate-free zone of the SOFT core at the end of the experiment, accompanied by a respective decrease in the δ13C signal of methane from -33.7‰ to -49.5‰. The involvement of methanogens in petroleum degradation was further confirmed by methane production in enrichment cultures from SOFT sediment after the addition of hexadecane, methylnapthalene, toluene, and ethybenzene. Petroleum degradation coupled to sulfate reduction was indicated by the increase of integrated sulfate reduction from 2.8 SO42- m-2 day -1 in untreated cores to 5.7 mmol SO42- m-2 day -1 in the SOFT core at the end of the experiment, accompanied by a respective accumulation of sulfide from 30 to 447 µM. Volatile hydrocarbons (C2 to C6 n-alkanes) passed through the methanogenic zone mostly unchanged and were depleted within the sulfate-reducing zone. The amount of non-volatile n-alkanes (C10 to C38) decreased step-wise towards the top of the sediment core and a preferential degradation of shorter (<C16) and longer chain n-alkanes (>C30) was seen during the seepage. This study illustrates, to the best of our knowledge, for the first time the development of methanogenic petroleum degradation and the succession of benthic microbial processes during petroleum passage in a whole round sediment core.